USE OF RAPD IN DETERMINING THE GENETIC RELATIONSHIP BETWEEN SOME SPECIES OF FAMILY PLANTS CUCURBITACEAE GROWING IN IRAQ - Hassn, N. T.; Al-Saffar, R. S.; Al-Muadhidi, A. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research was done to conducted to determine TEN taxa of the Cucurbitaceae family were studied using the RAPD approach to examine taxonomic relationships and genetic diversity, including Cucurbita pepo, Cucurbita maxima, Laganaria siceramia L.C.V. local, Laganaria siceramia L.C.V. Syria, Cucumis sativus, Cucumis melo, Cucumis melo flexuosus, Citrullus lanatus, Citrullus colocynthis, Luffa cylidrica, DNA of fresh leaves was extracted using modified protocol of Kit  due, invested DNA Marker based PCR technology using the RAPD Marker using Thirteen RAPD primers of (Operon) technology biologging to (Bio-RP1, Bio-RP2, Bio-RP3, Bio-RP4, Bio-RP5, Bio-RP6, Bio-RP7, Bio-RP8, Bio-RP9, Bio-RP10, UBC-13, OPC-12) sets.  , where explained the relationship between taxa on the basis of the appearance and disappearance of the bands and showed that differences in the location on the genomes of the studied cultivars on the agarose gel .As the primers generated (92) total bands resulting from (225) binding sites ,including (92 ) polymorphic binding sites distinct for the cultivars under study . To determine the interspecific among the investigated taxa, cluster analysis of the diversity matrices was carried out.